Shrouding add-on information: an experimental study - Tobias Wenzel; Hans-Theo Normann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We explore how competition affects firms obfuscation strategies in laboratory experiments. Firms sell a base good and an add-on product. The price of the add-on may be shrouded and, if so, myopic consumers pay too much. Shrouding is an equilibrium but an unshrouding equilibrium coexists. In our experiments, competition matters in that only duopolistic markets are frequently shrouded whereas fourfirm markets are not. With repeated interaction, shrouding rates do not increase. However, the opportunities to shroud facilitate tacit collusion on the base good price for the duopolies: the unshrouding equilibrium serves as a credible punishment if deviations occur.
Keywords: L40; L41; C90; 330